STRATEGIES FOR MANAGING SCHOOL OPERATIONAL ASSISTANCE FUNDS IN OVERCOMING COMMUNICATION DISTORTIONS IN FINANCING AT SENIOR HIGH SCHOOL 3 PRABUMULIH - Selamet Prihatin; Kemas Badaruddin; Mardeli Mardeli; Ade Akhmad Saputra (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study aims to analyze the Strategy for Managing School Operational Assistance Funds (BOS) by the Principal in Overcoming Distortions in Financing Communication at Prabumulih State Senior High School 3, South Sumatra Province. This research is a qualitative research, In collecting data, researchers used several collection techniques, namely, in-depth interviews, observation, and documentation. The data analysis technique uses the Miles and Huberman Model which consists of three stages, namely: data reduction, data display, and drawing conclusions or verification. Based on the results of the research in this study, in order for the implementation of the financing of the School Operational Assistance Fund (BOS) in overcoming the distortion of financing communication, several aspects need to be carried out, including; aspects of flexibility in the use of BOS funds, aspects of effectiveness in the use of BOS funds, aspects of efficiency in the use of BOS funds, aspects of accountability in the use of BOS funds and aspects of transparency of BOS funds.